1993
DOI: 10.3758/bf03211170
|View full text |Cite
|
Sign up to set email alerts
|

Working memory and strategies in syllogistic-reasoning tasks

Abstract: It has often been asserted that working-memory limitations are a major factor contributing to problem difficulty; for example, Johnson-Laird's (1983) mental-models theory appeals to workingmemory limitations to explain the difficulty of syllogistic reasoning. However, few studies have directly explored working memory in problem solving in general or syllogistic reasoning in particular. This paper reports two studies. In the first, working-memory load was varied by presenting syllogistic tasks either verbally o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
129
4
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(151 citation statements)
references
References 28 publications
15
129
4
2
Order By: Relevance
“…The latter results are in line with previous research showing that neither brief interruptions (Glanzer, Dorfman, & Kaplan, 1981) nor a three-digit working memory load (Baddeley & Hitch, 1974), while reading, has any significant effect on comprehending the material. The result of Study III, Experiment 1, however, appears to contradict a previous finding (Gilhooly et al, 1993) which asserted that the phonological loop only played a minor role in syllogistic reasoning. On closer inspection of the methodology and model used by Gilhooly et al (1993), the findings do not seem so disparate, but rather warrant a reinterpretation of the their interpretations.…”
Section: Introduction To Conclusioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The latter results are in line with previous research showing that neither brief interruptions (Glanzer, Dorfman, & Kaplan, 1981) nor a three-digit working memory load (Baddeley & Hitch, 1974), while reading, has any significant effect on comprehending the material. The result of Study III, Experiment 1, however, appears to contradict a previous finding (Gilhooly et al, 1993) which asserted that the phonological loop only played a minor role in syllogistic reasoning. On closer inspection of the methodology and model used by Gilhooly et al (1993), the findings do not seem so disparate, but rather warrant a reinterpretation of the their interpretations.…”
Section: Introduction To Conclusioncontrasting
confidence: 56%
“…The result of Study III, Experiment 1, however, appears to contradict a previous finding (Gilhooly et al, 1993) which asserted that the phonological loop only played a minor role in syllogistic reasoning. On closer inspection of the methodology and model used by Gilhooly et al (1993), the findings do not seem so disparate, but rather warrant a reinterpretation of the their interpretations.…”
Section: Introduction To Conclusioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Recent experimental (Carpenter et al, 1990;Gilhooly et al, 1993) and correlational (Kyllonen & Christal, 1990) research provides some direct evidence for a link between working memory capacity and Gf. Carpenter et al (1990) showed that an important determinant of performance on the Raven Advanced Progressive Matrices Test (Raven, 1965), a common marker for Gf, is the ability to simultaneously generate, evaluate and maintain goals in working memory.…”
Section: Nomothetic Span Of the Sctmentioning
confidence: 99%
“…The SCT was designed to measure the regulation of processes in working memory. Working memory is a system for the temporary storage and processing of information and is used in a broad range of everyday cognitive tasks (e.g., Baddeley, 1986;Gilhooly, Logie, Wetherick, & Wynn, 1993;Hitch, 1978).…”
Section: Theoretical Background Of the Sctmentioning
confidence: 99%